KARAKTERISASI GULA CAIR BATANG SORGUM (Sorgum sp.) - Endang Noerhartati; Tri Rahayuningsih (JURNAL AGROTEKNOLOGI, 2013)
The research aims to obtain the characteristics of sap and liquid sugar stem sorghum, using a randomized block design (RAK) 1 factors, raw materials (P), P1: white stem (KD4) height of 300 m; P2: red stem (Sorghum bicolor) 600 m , P3: red stem (Sorghum bicolor) 900 m. Extraction method refers to the results of research Noerhartati (2012), the best extraction K1P1 (use of lime 1000 ppm: flocculant 1000 ppm). Observations sap and liquid sugars were yield, pH, viscosity, color and turbidity visually and using tools Tintometer Model E, organoleptic parameters of taste, aroma, color, and viscosity, as well as components of liquid sugar. Analysis of data were observation of color, turbidity, and sugar components using descriptive analysis, yield, pH and brix using analysis of variance test followed duncan 5%; organoleptic tests using Friedman test. The results of characteristics of sap and liquid sugar (1) P1, Sap: yield=40%, baggase=59,5%, brix=11,30, pH=4,7; liquid sugar: 60% flavor and aroma score of 5 (most like), 40% color and viscosity score of 4 (like); yield=43,4%, blotong=11,5%, brix=68,30, pH=6,8, the component sugars: glucose=32.125 ppm, fructose=147.541 ppm , sucrose=153.459 ppm, (2) P2: sap= 40,7%, baggase= 59,6%, brix = 14,30, pH=5,1 ; Liquid sugar: the taste and aroma 60% score 5, color and viscosity 40% score 4; yield=44,6%, blotong=11,7%, brix=67,70, pH=6,9 , glucose=31.075 ppm, fructose=290.398 ppm, sucrose=302.455 ppm, (3) P3: sap=40%, baggase=59,5%, brix=14,70, pH=5,1; sugar Liquid: 60% flavor and aroma score of 5, 58,8% color and 40% viscosity score of 4; yield=46,5%, blotong=11,2%, brix=69,30, pH=6,9, glucose=26.200 ppm, fructose=393.443 ppm, sucrose=413.504 ppm.Keywords: characterization, extraction, liquid sugar, sap, stem sorghum